Examining the Nexus Between Internships and Employability: A Bibliometric Perspective - Zakaria, Zaiza Norsuriati Zainal; Awang, Yunita; Nasir, Noor Emilina Mohd; Taib, Azuraidah (Advances in Social Sciences Research Journal, 2024)
Internship is one of the beneficial platforms for students’ engagement in the real-working experience. The internship allows the interns to explore the potential job tasks expected in their field of interest. Interns can develop their employability or job-readiness skills namely communication, teamwork and critical thinking. From the employers’ perspective, the internship provides the potential cost saving in the workflow, particularly when assistance from temporary staff is needed, gives access to a new talent pool and facilitates the recruitment of prospective full-time employees. The employability of fresh graduates promotes industrial growth, sustainability, and economic development of the country. Internships may influence employability as students’ employability skills are enhanced through internships. For a better understanding of this issue, the current study examines the evolution of research publications on the nexus between internship and employability. Using bibliometric analysis of data from the Scopus database for a period from 1975 to 2024, this study explores the trends in research publications to determine document type, subject area, publication categories by authors and countries, citation metrics and keywords. A total of 246 pertinent documents were reviewed on 14 July 2024, and the data was evaluated using Microsoft Excel, VOSviewer, and Harzing's Publish or Perish. This study provides some insights into the trends and future development of the influence of internships on employability topics in the academic literature of Business, Management, and Accounting; Economic, Econometrics and Finance and Social Sciences. The findings of the study may also be beneficial to the university management for curriculum-related purposes, and to the employers for future recruitment planning.